Germline variation in NCF4, an innate immunity gene, is associated with an increased risk of colorectal cancer. Issue 6 (14th November 2013) - Ryan, Bríd M.; Zanetti, Krista A.; Robles, Ana I.; Schetter, Aaron J.; Goodman, Julie; Hayes, Richard B.; Huang, Wen‐Yi; Gunter, Mark J.; Yeager, Meredith; Burdette, Laurie; Berndt, Sonja I.; Harris, Curtis C.
<x xml:space="preserve">Abstract</x> Chronic inflammation has been implicated in the etiology of colorectal adenoma and cancer; however, few key inflammatory genes mediating this relationship have been identified. In this study, we investigated the association of germline variation in innate immunity genes in relation to the risk of colorectal neoplasia. Our study was based on the analysis of samples collected from the prostate, lung, colorectal and ovarian (PLCO) Cancer Screening Trial. We investigated the association between 196 tag single nucleotide polymorphisms (SNPs) in 20 key innate immunity genes with risk of advanced colorectal adenoma and cancer in 719 adenoma cases, 481 cancer cases and 719 controls. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CIs). After Bonferroni correction, the AG/GG genotype of rs5995355, which is upstream of NCF4, was associated with an increased risk of colorectal cancer (OR = 2.43, 95% CI = 1.73–3.39; p < 0.0001). NCF4 is part of the NAPDH complex, a key factor in biochemical pathways and the innate immune response. While not definitive, our analyses suggest that the variant allele does not affect expression of NCF4, but rather modulates activity of the NADPH complex. Additional studies on the functional consequences of rs5995355 in NCF4 may help to clarify the mechanistic link between inflammation and colorectal cancer.